DEVELOPMENT OF SPATIAL THINKING BASED STUDENT WORKSHEET IN GEOGRAPHY SUBJECT AT SMA NEGERI 1 RANDANGAN - Hubaib, Nurmuhniyanti M; Maryati, Sri; Koem, Syahrizal (Universitas Sebelas Maret (UNS), 2024)
This research is based on the issue of the lack of teaching materials in the form of spatial thinking-based student worksheets to assist students' learning process. Another issue is that we have not yet implemented student worksheets based on spatial thinking in teaching. This research aims to develop spatial thinking-based student worksheets based on primary map knowledge material to make the learning process innovative and meet the demands of the independent curriculum, which was reviewed from the spatial thinking element for X Grade students at SMA Negeri 1 Randangan. This research uses the Steven J. McGriff version of the ADDIE development model (analysis, design, Development, implementation and evaluation). The research subjects are students from X Grade in Natural Science (IPA) 2 and Social Sciences (IPS) 2 classes. The data are collected through tests and questionnaires. The researcher uses effect size analysis to determine the learning effectiveness using the spatial thinking-based student worksheets based on basic map knowledge material. The study results show the student's responses to the spatial thinking-based student worksheet, which is suitable for use and interesting for students. The effectiveness of learning using the spatial thinking-based student worksheets get value of value 0,34 implies categorized as effective with a moderate classification level. This shows that spatial thinking-based student worksheets are declared effective in learning geography based on basic knowledge of maps.